Altered Distribution of Peripheral Blood Maturation‐Associated B‐Cell Subsets in Chronic Alcoholism. (4th July 2015) - Almeida, Julia; Polvorosa, Maria Angeles; Gonzalez‐Quintela, Arturo; Madruga, Ignacio; Marcos, Miguel; Pérez‐Nieto, Maria Angeles; Hernandez‐Cerceño, Maria Luisa; Orfao, Alberto; Laso, Francisco Javier
<x xml:space="preserve">Abstract</x> Background Although decreased counts of peripheral blood (PB) B cells—associated with an apparently contradictory polyclonal hypergammaglobulinemia—have been reported in chronic alcoholism, no information exists about the specific subsets of circulating B cells altered and their relationship with antibody production. Here, we analyzed for the first time the distribution of multiple maturation‐associated subpopulations of PB B cells in alcoholism and its potential relationship with the onset of liver disease. Methods PB samples from 35 male patients—20 had alcoholic hepatitis (AH) and 15 chronic alcoholism without liver disease (AWLD)—were studied, in parallel to 19 male healthy donors (controls). The distribution of PB B‐cell subsets (immature/regulatory, naïve, CD27− and CD27+ memory B lymphocytes, and circulating plasmablasts of distinct immunoglobulin—Ig—isotypes) was analyzed by flow cytometry. Results Patients with AH showed significantly decreased numbers of total PB B lymphocytes (vs. controls and AWLD), at the expense of immature, memory, and, to a lesser extent, also naïve B cells. AWLD showed reduced numbers of immature and naïve B cells (vs. controls), but higher PB counts of plasmablasts (vs. the other 2 groups). Although PB memory B cells were reduced among the patients, the percentage of surface (s)IgA+ cells (particularly CD27−/sIgA+ cells) was increased in AH, whereas both sIgG+ and sIgA+ memory B cells were significantly overrepresented in AWLD versus healthy donors. Regarding circulating plasmablasts, patients with AH only showed significantly reduced counts of sIgG+ cells versus controls. In contrast, the proportion of both sIgA+ and sIgG+ plasmablasts—from all plasmablasts—was reduced in AH and increased in AWLD (vs. the other 2 groups). Conclusions AH and AWLD patients display a significantly reduced PB B‐cell count, at the expense of decreased numbers of recently produced immature/regulatory B cells and naïve B cells, together with an increase in Ig‐switched memory B lymphocytes and plasmablasts, particularly of IgA+ cells.